Pterygoid implants for the immediate rehabilitation of the atrophic maxilla: A case report of a full arch on 4 implants - Bernardo Luz Nunes de Sousa (Oral and Maxillofacial Surgery Cases, 2020)
Pterygoid implants are a valid and valuable resource for the rehabilitation of the posterior atrophic maxilla and have been detailed before in the literature. Nonetheless, the full arch rehabilitation with immediate loading of the upper jaw with 4 implants, where the 2 anterior ones are conventional implants and the 2 posterior ones are pterygoid implants has not been addressed in any paper according to the author's best knowledge. In this case report, the authors present this technique performed on a 68-year old woman with atrophic maxilla looking for a fast, non-invasive full-arch fixed solution. A screw-retained acrylic FP3 provisional was installed 6 hours after surgery and a titanium milled/acrylic prosthesis was installed 4 months later. The patient has been recalled for 1,5-years with successful follow-up both on implants and prothesis. The presented technique seems to be a valid solution for the full arch rehabilitation with immediate loading of the atrophic maxilla, avoiding more invasive and time-consuming procedures like the sinus lift, bone regeneration or zygomatic implants.